Comparison of the Effectiveness of Transdiagnostic Treatment and Management of Burnout on Emotional Experience towards Spouse in Married Women - Ghodrati Isfahani, Zohreh; Atashpour, Seyed Hamid; Yousefi , Zahra (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: This research aimed to compare the effectiveness of transdiagnostic treatment and marital burnout management on the emotional experience towards the spouse in married women of Isfahan. Materials and Methods: The present study was a quasi-experimental pre-test, post-test, follow-up design. The statistical population consisted of married women with a minimum of 10 years of marital life. Forty-eight individuals were selected through purposive sampling based on inclusion and exclusion criteria and randomly assigned to two experimental groups and one control group. While the control group received no training, the experimental groups each underwent 10 sessions of 90 minutes according to the respective protocols (Unified transdiagnostic Treatment by Barlow et al., (2010) and the Marital Burnout Management Training Package by the authors. All three groups filled out the Emotional Experience Towards Spouse Questionnaire in three stages: pre-test, post-test, and follow-up. Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (repeated measures analysis of variance and Bonferroni post-hoc test) with SPSS-25. Findings: The results indicated that both transdiagnostic treatment and marital burnout management, as compared to the control group, significantly reduced overall negative emotional experience and increased positive emotional experience towards the spouse. However, in reducing negative emotional experience, transdiagnostic treatment was more effective. Conclusion: Both transdiagnostic treatment and marital burnout management are effective in improving the emotional climate in marital relationships of women experiencing long-term marriages. They contribute significantly to reducing negative emotions and fostering positive emotional experiences towards the spouse. Transdiagnostic treatment, in particular, shows greater efficacy in diminishing negative emotional experiences, indicating its potential as a robust approach in marital interventions. These findings underscore the importance of applying targeted therapeutic approaches to enhance marital satisfaction and emotional well-being